Modification of the UTAUT Model: The Mediation Role of the J-Kopi Application and Moderation of Transformational Leadership on Smart City Acceptance in Regional Apparatus Organizations in Jember District - Wardah Qurrotul'Ain; Toni Herlambang; Amalina Maryam Zakiyyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of transformational leadership and technology utilization on smart city acceptance by integrating humanistic aspects as a mediating variable within the Regional Apparatus Organizations (OPD) of Jember Regency. The background of this study stems from the Jember Regency Government’s effort to implement the “Jember Kota Pintar” (J-KOPI) application as a digital innovation to realize smart city-based governance. This research employed a quantitative approach using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software. The population consisted of civil servants (ASN) within Jember Regency’s OPD, with 110 respondents selected through purposive sampling. The results show that transformational leadership has a significant effect on the integration of humanistic aspects, technology utilization, and smart city acceptance. Furthermore, technology utilization has a significant positive effect on smart city acceptance. The integration of humanistic aspects mediates the relationship between transformational leadership and smart city acceptance. These findings highlight that the success of smart city implementation is not solely determined by technological readiness, but also by human values and leadership styles that inspire change. The implications of this study emphasize the importance of transformational leadership and human-centered integration in optimizing technology adoption in the public sector, particularly in the implementation of the J-KOPI-based smart city in Jember Regency.